2020
DOI: 10.1093/jisesa/ieaa081
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Coexisting Species and the First Known Case of a Cheater in Epicephala (Gracillariidae) Associated with a Species of Glochidion (Phyllanthaceae) in Tropical Asia

Abstract: Glochidion plants and Epicephala moths played different roles and kept the balance in the mutualism. We studied the four coexisting Epicephala species on Glochidion sphaerogynum in detail and reconstructed the phylogenic tree of 40 Gracillariidae species. The results showed that one of them (Epicephala impolliniferens) did not pollinate G. sphaerogynum, because of lacking the specialized structure of carrying pollen. These results suggested that E. impolliniferens acted as a ‘cheater’ in the system. The phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, because the mutualistic relationship has evolved several times in tribe Phyllantheae , there could be differences in morphological adaptations or similar morphological patterns in the different groups could have arisen through convergent evolution. Recent studies have shown that the mutualism between leafflowers and leafflower moths is more complex than first described ( Kato et al 2003 ) as there are differences in the level of species specificity ( Kawakita and Kato 2004a , 2006 ; Zhang et al 2012 ; Li et al 2015 ; Yang and Li 2018 ), cheaters of the mutualism ( Kawakita et al 2015 ; Wang et al 2020 ) and defences against this antagonistic relationship ( Goto et al 2010 ; Furukawa and Kawakita 2017 ). Furthermore, possible reversals in flowers are indicated here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the mutualistic relationship has evolved several times in tribe Phyllantheae , there could be differences in morphological adaptations or similar morphological patterns in the different groups could have arisen through convergent evolution. Recent studies have shown that the mutualism between leafflowers and leafflower moths is more complex than first described ( Kato et al 2003 ) as there are differences in the level of species specificity ( Kawakita and Kato 2004a , 2006 ; Zhang et al 2012 ; Li et al 2015 ; Yang and Li 2018 ), cheaters of the mutualism ( Kawakita et al 2015 ; Wang et al 2020 ) and defences against this antagonistic relationship ( Goto et al 2010 ; Furukawa and Kawakita 2017 ). Furthermore, possible reversals in flowers are indicated here.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology of staminate and pistillate flowers changed and adapted accordingly (for example, see Zhang et al (2012) ; Yang and Li (2018) ). The female moths of mutualistic species actively collect pollen from staminate flowers, whereby the sensilla or setae (hairs) on the proboscis sweep up the pollen (these hairs are absent in male moths and in (cheating) moths with no mutualistic relationship; Kato and Kawakita (2017) ; Yang and Li (2018) ; Wang et al (2020) ). The female moths then place the pollen on the stigmas of the pistillate flowers and finally place an egg either between the calyx and the ovary, or in the ovary by drilling through the stigma or through the ovary wall ( Kato et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%